2005
DOI: 10.1002/path.1859
|View full text |Cite
|
Sign up to set email alerts
|

How ischaemic preconditioning protects small liver grafts

Abstract: Interleukin-1 (IL-1) and transforming growth factor-beta (TGFbeta) are key inhibitors of hepatocyte proliferation after hepatectomy. IL-1 inhibition by heat shock proteins (HSPs) has been reported in inflammatory processes. A recent study indicated the benefits of ischaemic preconditioning in reduced-size orthotopic liver transplantation (ROLT). The present study examined: (a) the effect of ischaemic preconditioning on IL-1 and TGFbeta in ROLT; (b) whether preconditioning protects small liver grafts through HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 62 publications
1
60
3
Order By: Relevance
“…Previous studies have shown that the release of IL-1 is potentially influenced by NO during IRI in a variety of cell types [157][158][159] . In IPC-treated rats that underwent reduced size liver transplantation, an increase in IL-1α levels were noted following NO synthesis inhibition [150] . This practice abolished the benefits of IPC on hepatic IRI, oxidative stress and liver regeneration [3,150] .…”
Section: Down-regulation Of Inhibitory Mediators Of Liver Regenerationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the release of IL-1 is potentially influenced by NO during IRI in a variety of cell types [157][158][159] . In IPC-treated rats that underwent reduced size liver transplantation, an increase in IL-1α levels were noted following NO synthesis inhibition [150] . This practice abolished the benefits of IPC on hepatic IRI, oxidative stress and liver regeneration [3,150] .…”
Section: Down-regulation Of Inhibitory Mediators Of Liver Regenerationmentioning
confidence: 99%
“…In IPC-treated rats that underwent reduced size liver transplantation, an increase in IL-1α levels were noted following NO synthesis inhibition [150] . This practice abolished the benefits of IPC on hepatic IRI, oxidative stress and liver regeneration [3,150] . Further more, the detrimental effects of NO inhibition were not observed when rats subjected to this treatment were subsequently treated with an IL-1 receptor antagonist (IL-1-RA) [150] .…”
Section: Down-regulation Of Inhibitory Mediators Of Liver Regenerationmentioning
confidence: 99%
See 3 more Smart Citations